A novel 3D skeletal frame topology for energy harvesting systems. (January 2019) - Fattahi, Iman; Mirdamadi, Hamid Reza
Abstract: The topology of energy harvesters (EHs) are typically designed to operate at resonance in the first bending mode when subjected to translational excitations in a single direction. However, their topologies are inappropriate for torsional as well as bi-directional translations abundantly found in environment. A novel 3D EH is proposed and compared to the cantilevered ones. Both topologies are modeled in ABAQUS with vibration analyses to make comparisons. The novel topology has a desired performance in translational excitations in a 2D plane along with torsional excitations. Moreover, the 3D skeletal frame harvester undergoes high strains at both ends making it more efficient due to the fact that piezoelectric materials produce voltage in response to strain. A validation is also performed for the ABAQUS model against theoretical and experimental results. As another advantage, the occupied volume of the introduced EH and the surfaces of the tip mass can be utilized for circuit boards or other electronic components resulting in a more compact EH.